GIS-Based Analysis of Wildfire Distribution Across Slopes in the Wadi Safsaf Watershed, Northeastern Algeria - Tout, Faicel; Rebouh, Nouh; Benzid, Yacine; Zouak, Zakaria; Zeghmar, Amer; Bourecherouche, Meriem; Dinar, Haythem; Keblouti, Sara (Banko Janakari, 2025)
In recent decades, many regions of the world have been affected by wildfires. As a result, researchers have shown increasing interest in understanding the causes of these events, their patterns of spread, and the factors that influence their behaviour. This study aimed to investigate the distribution of wildfire affecting vegetation on slopes in the Wadi Safsaf watershed in Algeria using Geographic Information Systems (GIS). The research focused on analysing the relationship between slope and area affected by wildfires by comparing the Differential Normalised Burn Ratio (dNBR) with slope maps. The study also used the Normalised Difference Vegetation Index (NDVI) and the Land Use and Land Cover (LULC) map in additional stages to gain a deeper understanding of the results. Interestingly, the results showed that, contrary to initial expectations, areas with low slopes had the highest percentage of wildfire damage. Further analysis revealed that most of the affected areas were agricultural land that had been misclassified as burned by the (dNBR). The research underlines the importance of field verification and highlights the role of slope in increasing wildfire damage in forested areas. However, it also emphasises the complexity of the relationship between slope and wildfire spread, which is influenced by other factors. The study concludes by recommending the consideration of multiple environmental factors in the study of this phenomenon. It advocates the development of more accurate predictive models to support disaster management decision-making.